Judical independence and the validity of converted elections - Raphaël Franck (Bar-Ilan University, Department of Economics, 2009)
This article examines whether the judges of the French Constitutional Court demonstrated partisanship when ruling on the validity of the elections to the lower house of the French Parliament between 1958 and 2005. It uses a new dataset on the decisions of the Constitutional Court which takes into account the characteristics of the controverted parliamentary elections. The rulings of the Constitutional Court are found to be biased against far-right candidates. However, the judges are also found to display some form of independence vis-à-vis the government since they do not favor candidates from the ruling party when they render their decisions.
Keywords: D72; D73; H11; 330; Judicial independence; Judicial politics; Judges; Parliamentary elections; Wahl; Parlament; Rechtsprechung; Verfassungsgericht; Neue politische Ökonomie; Frankreich